Ground state properties of charmed hypernuclei within a mean field approach - Guven, H.; Bozkurt, K.; Khan, E.; Margueron, J. (AMER PHYSICAL SOC, 2021)
Closed shell charmed hypernuclei Li-5(Lambda c), F-17(Lambda c) , (Lambda cSC)-S-41 , (57)(Lambda c) Cu, Sb-133(Lambda c), and Bi-209(Lambda c) are calculated within the Hartree-Fock approach by using three different force sets derived from microscopic Brueckner-Hartree-Fock calculations of A hypernuclei. Ground state properties (binding energies, Lambda(c) separation energies, Lambda(c) single particle energies, and Lambda(c) densities) of charmed nuclei are examined. We confirm the results and conclusions of different models from the literature, related to Lambda(c) hypernuclei. Due to the Coulomb repulsion between protons and the Lambda(c) baryon, charmed hypernuclei are most bound for 16 <= A <= 41, where F-17(Lambda c) can be considered as an excellent candidate to determine charmed hypernuclei properties. The competition between the attractive nucleon-A s interaction and the Coulomb repulsion is discussed, and we compare Lambda and Lambda(c) hypernuclei properties.
Keywords: NUCLEI; SUPERNUCLEI; Physics